KOMUNIKASI TRANSDENTAL PENGANUT KAPITAYAN DALAM PENINGKATAN KESADARAN SPIRITUAL - Muhammad Iqbal Yaqin; Faris (Commed : Jurnal Komunikasi dan Media, 2022)
This study intend to examine how the analysis of the transdental communication of Kapitayan disciple to increasing spiritual awareness carried out by the Damar village community, using the perspective of the Transdental Communication. Research on Transdental Communication on Javanese spiritual awareness is very interesting to study considering that research on spiritual awareness is also still rarely done in scientific research, especially in the focus of Communication Science. Method in this study uses descriptive qualitative research methods. The results of this study indicate that humans in their lives always face various kinds of difficulties. So to deal with these problems, humans draw closer to the Almighty through a spiritual journey. Spiritual awareness is a science that discusses the condition of the human mindset which is manifested by the soul. as the essence and existence of human life. Spiritual awareness connects humans to interact between servants and their God through energy and spirituality in each human being. as well as communication as an interaction process that